Intergenerational Influences on the Receipt of Unemployment Insurance in Canada and Sweden - Miles Corak; Björn Gustafsson; Torun Österberg (Institute for the Study of Labor (IZA), 2000)
The objective of this paper is to examine the extent to which an individual?s use of unemployment insurance (UI) as a young adult is influenced by past experience with the program, and by having had a parent who also collected UI. A major methodological challenge is to determine the extent to which the intergenerational correlation of UI status is ?spurious? or causal. Both the time to a first UI claim and the entire sequence of claims over an extended period are examined using two alternative ways of controlling for unobserved heterogeneity. The analysis is based upon longitudinal data on a cohort of young Canadian and Swedish men. It is found that parental use of UI shortens the time to a first UI claim in Canada, but not in Sweden. Subsequent participation in the Canadian program is influenced by parental UI history. In Sweden individual learning through past participation in UI?not family background?is the dominant avenue determining repeated participation.
Keywords: I38; J62; J65; 330; Unemployment insurance; intergenerational mobility; unemployment; Arbeitslosenversicherung; Generationenbeziehungen; Arbeitslosigkeit; Familiensoziologie; Schätzung; Schweden; Kanada